Quality Control Using Statistical Processing Control (SPC) Method on Tensile Testing Results of Metallic Materials - Boangmanalu, Eka Putra Dairi; Pratama, Angga Bahri; Saragi, Jandri Fan HT; Sahat, Sahat (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to evaluate the quality of tensile testing conducted at the Mechanical Engineering Laboratory of Politeknik Negeri Medan. Based on the results of attribute inspection, there were 42 units of material defects with a value of 0.124260355. The Upper Control Limit (UCL) was 0.415734865, and the Lower Control Limit (LCL) was 0.0167214 or 0. The subsequent check sheet showed that 34 test specimens did not meet the standard. The value was 0.0100591716, the UCL was 0.03631557869, and the LCL was 0.00362 or 0. The next check sheet revealed 25 failed tests with a value of 0.0073964497, a UCL of 0.0299413849, and an LCL of -0.0151484 or 0. This study aims to evaluate the quality of tensile testing conducted at the Mechanical Engineering Laboratory of Politeknik Negeri Medan. Based on the results of attribute inspection, there were 42 units of material defects with a value of 0.124260355. The Upper Control Limit (UCL) was 0.415734865, and the Lower Control Limit (LCL) was 0.0167214 or 0. The subsequent check sheet showed that 34 test specimens did not meet the standard. The value was 0.0100591716, the UCL was 0.03631557869, and the LCL was 0.00362 or 0. The next check sheet revealed 25 failed tests with a value of 0.0073964497, a UCL of 0.0299413849, and an LCL of -0.0151484 or 0.